2022
DOI: 10.1007/s10816-021-09547-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Lipid Profiles and Use of Ethnographic Pottery: an Exploratory Study

Abstract: Investigating the organic content of archaeological pottery has largely focused on identifying food commodities, but their use and mode of processing still need to be thoroughly investigated. The present study aims to explore the diversity of organic residue absorption patterns, over a wider range of functions than previously studied by experimentation, by analysing ceramics still in use today. A field survey in Bedik Country, Senegal, where the use of pottery is still alive, was conducted to document the uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…We note that there was a surprising level of variation in lipid concentration between replicates of identical input ingredients and weight. This revealed that in addition to the impact of cooking practice and frequency of use [50], even identically processed foodcrusts are not homogenous. However due to the small sample size it was not possible to reveal the impact of lipid content on protein detection (supplementary text S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that there was a surprising level of variation in lipid concentration between replicates of identical input ingredients and weight. This revealed that in addition to the impact of cooking practice and frequency of use [50], even identically processed foodcrusts are not homogenous. However due to the small sample size it was not possible to reveal the impact of lipid content on protein detection (supplementary text S5).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to proteomics, there is a diversity of published experiments exploring how lipids derived from different ingredients respond to a range of cooking and deposition practices [for example 44,[45][46][47][48][49][50]. For instance, Miller et al [44] demonstrate that absorbed lipids extracted from ceramics represent a long period of use, while surface deposits represent the most recent cooking events.…”
Section: Potential Preservation Biasesmentioning
confidence: 99%
“…Lipid concentrations from fragments belonging to the same vessel were compared to (1) assess the reliability of lipid concentration values obtained and (2) measure the gradient of lipid concentration across the vessel profile to make inferences about vessel use, if possible (Table 3). Such work has previously been carried out on ethnographic ceramic vessels from Senegal (Drieu et al, 2022). Table 3 shows that fragments belonging to the same Indus BSJ demonstrate a relatively constrained range of values for lipid yields.…”
Section: Lipid Yields From Different Groups Of Potterymentioning
confidence: 99%
“…; e.g. [12][13][14][15]). Very detailed information is sometimes obtained by microscopic observation of charred residues on the surfaces of ceramic vessels (e.g.…”
Section: The Challenge Of a Multidisciplinary Approach Of Foodways In...mentioning
confidence: 99%